Neuroparenting Book Development: Stimulation of Children’s Brain Development - Maulidya Ulfah; Sekar Ayu Aryani; Maemonah Maemonah (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
This research aims to yield a neuroparenting book as the nurture model for stimulating children's development that is appropriate to be used by parents. The result of need analysis finds that parents are not yet optimal in stimulating the child’s development with various activities. Neuroparenting is a form of nurturing that optimizes the development of the brain. The methods used are the Research and Development 4-D model. The product is validated by experts and is trialed with 40 parents. The data gathering techniques are observation, questionnaires, interviews, and documentation. The analysis while disseminating the questionnaire was through descriptive analysis, and the product quality was through quantitative data analysis. The development of the book’s content includes nurture, child’s characteristics, positive upbringing, parents’ emotions, effective communication, child’s activities, health, and character building. This study shows that the result of the neuroparenting book is declared to be very appropriate to use, with the result from media experts at 84,67%, material experts at 84.33%, and language experts or linguists at 88,67%. Based on trials, this book has benefits for parents in order to increase the knowledge, attitudes and skills of the community in stimulating children's growth and development.